Impact of binge drinking during college on resting state functional connectivity. (1st October 2021) - Tong, Tien T.; Vaidya, Jatin G.; Kramer, John R.; Kuperman, Samuel; Langbehn, Douglas R.; O'Leary, Daniel S.
Highlights: Investigated longitudinal effects of binge drinking on brain connectivity. Examined canonical brain networks and edge level predictive modeling. Change in Default Mode-Ventral Attention connectivity linked to longitudinal binge drinking frequency. Longitudinal binge drinking could not be predicted by change in edge-level connectivity using cross-validation. Abstract: Aim: The current study examined the longitudinal effects of standard binge drinking (4+/5+ drinks for females/males in 2 hours) and extreme binge drinking (8+/10+ drinks for females/males in 2 hours) on resting-state functional connectivity. Method: 119 college students (61 males) were recruited in groups of distinct bingeing patterns at baseline: non-bingeing controls, standard and extreme bingers. Resting-state scans were first obtained when participants were freshmen/sophomores and again approximately two years later. Associations between longitudinal bingeing (reported during this two-year gap) and network connectivity were examined. Network connectivity was calculated by aggregating all edges affiliated with the same network (an edge is a functional connection between two brain regions). The relationship between longitudinal bingeing and connectivity edges was also studied using connectome-based predictive modeling (CPM). Results: Greater standard bingeing was negatively associated with change in connectivity between Default Mode Network and Ventral Attention Network (DMN-VAN; False Discovery Rate corrected), controlling for initial binge groups, longitudinal network changes, motions, scanner, SES, sex, and age. The correlations between change in DMN-VAN connectivity and change in cognitive performance (Stroop, Digit Span, Letter Fluency, and Trail Making) were also tested, but the results were not significant. Lastly, CPM failed to identify a generalizable predictive model of longitudinal bingeing from change in connectivity edges. Conclusions: Binge drinking is associated with abnormality in networks implicated in attention and self-focused processes, which, in turn, have been implicated in rumination, craving, and relapse. More extensive alterations in functional connectivity might be observed with heavier or longer binge drinking pattern.